Pemanfaatan Teknologi Digital dalam Meningkatkan Minat Belajar Bahasa Indonesia Siswa di Sekolah Dasar - Nayla Adhwa; Nurul Faeza; Nur Azmi Alwi; Salmaini Safitri Syam (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study examines how digital technology can help boost elementary school students’ interest in learning the Indonesian language. As technology continues to influence the way education is delivered, incorporating digital tools into the classroom has become increasingly important. The study examines how interactive learning techniques, including educational games, digital storytelling, and multimedia presentations, can enhance the engagement and enjoyment of language learning for elementary students. A qualitative descriptive methodology was used, with data collected through interviews with both teachers and students, classroom observations, and the review of relevant documents. The results indicate that digital technology significantly contributes to increasing students' motivation, participation, and curiosity. Interactive digital tools foster a more lively and enjoyable learning atmosphere, making it easier for students to grasp and relate to the content. Teachers also reported that students became more active during lessons and demonstrated improved comprehension and vocabulary usage.The study concludes that integrating digital technology into Indonesian language lessons can shift traditional teaching methods toward more student-centered and engaging learning. It is recommended that schools invest in proper digital infrastructure and provide training for teachers to fully benefit from interactive learning approaches